Knowledge, attitude and practices regarding HIV/AIDS among the community of Rawalpindi and Islamabad, Pakistan - Ali, Muhammad Ghafoor; Ahmad, Muhammad Owais (International Journal of Research in Medical Sciences, 2017)
Background: The study was conducted to assess the awareness regarding Knowledge, Attitude and Practices about HIV/AIDS in the community of Rawalpindi and Islamabad. Methods: The study was conducted in Rawalpindi and Islamabad with age of 18 years and more. The data was randomly selected from 120 people having qualification of undermatric/matric/graduation/masters and above through questionnaire. The duration of the study was one year from April 2012 to March 2013. Results: Study showed that media is major source of awareness through Television (81.7%) and News Paper (67.5%).It was seen that 48.3% knew the difference between HIV and AIDS. 53.3% knew the signs and symptoms of HIV/AIDS but more than 46% did not know clinical features. Most of the community (79.2%) knew about the mode of transmission but small percentage (20.8%) did not have knowledge about transmission of disease. 85.8% knew about mode of prevention of HIV/AIDS. More than 80% of the participants suggested for compulsory screening of HIV/AIDS whereas a small percentage (up to 20%) did not suggest. Attitude of community was mix reply with positive attitude (58.3%) and negative attitude (41.7%).About 40% were in favor of health insurance whereas around 60% feel no need of health insurance to the HIV/AIDS patients.70% of the participants recommended to maintain the confidentiality of patient while 30% gave negative reply. Community was opinion that health awareness would reduce (96.7%) the risk of disease while only a small percentage (3.3%) thought for having no impact on prevention. Conclusions: The study showed sufficient knowledge and awareness but negative attitude of community towards patients of HIV/AIDS.